Study of the effect of modulation of the refractive index nonlinear couplers in photonic crystals - Ana Gardennya Linard SÃrio Oliveira Mendes (2014)
This paper presents a numerical investigation of the propagation and cover (100fs) short pulse switching in a nonlinear coupler dual-core photonic crystal fiber with periodically modulated constructed fiber nonlinearity ( PMN - PFC ). Our main objective was to study the effect of amplitude modulations (AM) and frequency modulation (Wm) in the refractive index of nonlinearity (gamma) at a spread of Photonic Crystal Fiber with initially fixed range with frequency and amplitude periodically varying modulation. The implementation of modulation was inserted into dual-fiber couplers, which has been studied for its use as a whole using ultra switching optical switch and as an optical processor. Our simulations are taking into account the amplitude and frequency modulations of different PMN - PFC. Coupler for coupling whose length is Lc = 1.8 cm, the transmission characteristics of the compression factor , the crosstalk ( Xtalk ) and extinction rate ( Xratio ) levels were studied in the first descending order solitons of high energy pump for considering 2LC. An analysis of the reference (channel 2) channel was observed that the low frequency modulation is an increase in the switching power by increasing the transmission efficiency. For high modulation frequencies transmitted energy efficiency loses. The switching pulses are stronger in the low frequency and high amplitude modulation. The Xtalk is a function of the measurement made on the secondary channel (channel 1) revealed that this increase in unwanted high-frequency energy, to reduce the extent of amplitude modulation. In summary, we have demonstrated that the introduction of a non- linear profile leads to a frequency modulated PMN - PFC high variations in transmission efficiency , Xtalk , Xratio function of frequency and modulation amplitude and the input power.